Hubungan Instruksi Kerja dengan Unsafe Action pada Pekerja Ketinggian di Proyek Konstruksi Pembangunan SMK-SMAK Bogor Tahun 2023 - Raihan Muhammad Dzulkarnaen; Decy Situngkir; Ira Marti Ayu; Putri Handayani; Mayumi Nitami (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Work instructions are work procedures that are arranged sequentially to facilitate work related to work tools, mechanical hazards, physical hazards, chemical hazards and biological hazards. This research aims to determine the relationship between work instructions and unsafe actions among high-rise workers in the Bogor SMK-SMAK construction project in 2023. This research method uses an analytical cross sectional research design with the population size of this study being 62 workers with a sample size of 59 construction workers. Sampling used non-probability techniques using purposive sampling techniques with univariate and bivariate data analysis using the chi-square test. This research was conducted in May – December 2023. Univariate results showed that the highest proportion of workers had good work instructions, namely 32 respondents (54.2%). The results of statistical tests show that there is a relationship between work instructions (p-value 0.017) and unsafe actions among high-altitude workers. This research concludes that the more workers comply with work instructions, the safer their work behavior will be and vice versa.